O DESIGN NO PROCESSO DE GAMIFICAÇÃO: reabilitação de pacientes com sequelas motoras Pós-AVC. - ALVES, Larissa Karla Reis Sá (2019)
Games, digital games, are a popular form of entertainment among audiences of all ages. Brazil is the main gaming market in Latin America and thirteenth in the world ranking. With the expansion of games, emerged a new strand based on entertainment, called "serious games" that are intended to aid in learning or relearning in various areas such as linguistics, space, body-kinesthetic, rehabilitation of people, business training, among others. In this context, the present research, of a qualitative nature, with a descriptive-exploratory character, aimed to propose recommendations for structuring the graphic elements of the design in digital objects for motor rehabilitation of people with post-stroke sequelae. To do so, the methodology presents the identification and mapping of design elements in two gamut objects: D2R3D and Motion Rehab. Additionally, the research describes the perception of designers in the analysis of the objects under study. Based on the methodological procedure it was possible to create a set of 16 (sixteen) recommendations to guide the structuring of the graphic elements of the design in gamified digital objects.